A Proposal of a Reference Model for the Pharmaceutical PDP Management - Paula, de, Istefani Carísio; Ribeiro, José Duarte (Brazilian Journal of Operations & Production Management, 2010)
This paper presents a reference model for pharmaceutical Product Development Process. The model was created founded on renowned methods as Concurrent Engineering, Stage Gates and Product Based Business. It was developed using legislation and information from interviews with professionals of Brazilian pharmaceutical companies. The developed model contemplates three macro stages and seven phases, embracing from business opportunity recognition to product market launching. The purpose of this article is to introduce the reference model for the pharmaceutical body, since it represents an improvement compared to the general product development models presented in the literature. The reference model is also important in the pharmaceutical academic field, as a didactic tool.